Draft Eleventh Five Year Plan 2007-2012 and Annual Plan 2007-2008 Volume - II A Statistical Tables Government of Madhya Pradesh - Planning Commission (Planning Commission, 2007)
Proposed Outlays - Major Heads / Minor Heads of Development Proposed Outlay on Continuing and New Schemes (2002-07 and 2002-03 to 2005-06 Actual Expenditure) Proposed Outlay on Continuing and New Schemes(2006-07 and 2002-07 anticipated Expenditure) Proposed Outlay on Continuing and New Schemes(2007-12 & 2007-08).
Government of Madhya, Pradesh, Planning, Economics and Statistics Department